2020
DOI: 10.1002/ece3.7005
|View full text |Cite
|
Sign up to set email alerts
|

Plant phylogeny drives arboreal caterpillar assemblages across the Holarctic

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 90 publications
(180 reference statements)
3
14
0
Order By: Relevance
“…Our second mechanism predicted proportions of shelterbuilders, which are more specialised than exposed feeders (Seifert et al 2020b), to decline further into the growing season. However, proportional abundances of shelter-builders were only found to decrease in midseason.…”
Section: Discussionmentioning
confidence: 88%
“…Our second mechanism predicted proportions of shelterbuilders, which are more specialised than exposed feeders (Seifert et al 2020b), to decline further into the growing season. However, proportional abundances of shelter-builders were only found to decrease in midseason.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, we found increasing community dissimilarity with increasing phylogenetic distance between tree genera (Figure 3). Pairwise dissimilarities of communities of phytophagous insects increase with increasing phylogenetic distance between their host trees (Brändle & Brandl, 2006; Novotny et al, 2010; Seifert et al, 2020; Vialatte et al, 2010). Studies on saproxylic beetles have reported greater α‐diversity associated with evolutionarily non‐isolated trees, such as oaks, hornbeams ( Carpinus ) or elms ( Ulmus ) (Gossner et al, 2013, 2016; Müller, Wende, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among deciduous trees, oaks host the richest assemblages of insects in Europe (Brändle & Brandl, 2001; Southwood, 1961). Closely related hosts typically share physiological and chemical characteristics (Agrawal, 2007; Seifert et al, 2020; Whitfeld et al, 2012), which may also determine the composition of wood‐inhabiting fungi and bacteria communities (Moll et al, 2018). Therefore, lower variation of beetle assemblages between closely related trees might be the result of a shared species pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For insects, studies have suggested high correlations between phylogenetic structure and species cooccurrences across different areas (e.g. Ceccarelli et al 2020, Seifert et al 2020, Staab et al 2020). However, it is still unclear how phylogenetic distance and functional traits affect co-occurrence within two trophic levels (Gotelli & McCabe 2002, Kraft et al 2015.…”
Section: Introductionmentioning
confidence: 99%